The Significances of Signs in Local Riddle of Toraja - Emon Paranoan; Lewi Kabanga' (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Many forms of language can be used to measure our thinking ability. The different area has different way in communicating language. Karume or riddle is a language model that contains many signs, it is worthy to be preserved for the sake of cognition and creativity thinking of Toraja’s Millennium generation. This research aims to find the significances of local riddle, called karume, by using de Saussure’s theory that elaborates the idea of signifier, signified, and significance. For the further analysis, this research also investigates meaning of signs either denotatively or connotatively, the data then analyzed by combining both word-level analysis and sentence level analysis.  The method used in this research was a descriptive qualitative method. To obtain the data, the documentation technique was used. Firstly, the data downloaded from internet then translated lexically and contextually to get the cores that facilitated signifier and signified. In simplifying data analysis, the data was classified based on its forms and then put into a table and then the data analyzed structurally and denotatively-connotatively. The Result of this analysis revealed that there were three features of semiotics embodied in karume. They were 1. Analogy, 2. Language style, and 3. Entailment. They can be used to show referential significance of riddle in Toraja